Effect of concrete stress states on carbonation depth of concrete - Wang, Jian; Ng, Pui-Lam; Su, Han; Chen, Jiajian; Du, Jinsheng (Journal of Civil Engineering and Management, 2019)
Carbonation can lead to reduction of alkalinity of concrete and initiation of steel reinforcement corrosion. In durability design of concrete structures, the carbonation depth should be duly considered. However, the concrete stress state would influence the carbonation depth, and there has been inadequate research on such effect. In this study, it is proposed to introduce a stress influence coefficient to the concrete carbonation depth model. With reference to the experimental data from eleven research studies in the literature encompassing both tensile and compressive stress states, the relationship between stress influence coefficient and concrete stress ratio is quantitatively investigated, and mathematical equations relating the stress influence coefficient with the concrete stress ratio are established. Comparative study with three typical existing groups of equations shows that the proposed equations of stress influence coefficient are more reasonable and have a higher reliability. The effects of carbonation time, mix proportions of concrete on stress influence coefficient are also analysed, and the magnitudes of the effects are found to be approximately within ±10%. Finally, the modified carbonation depth models are proposed and verified by the experimental data, which suggests that the proposed models are of desirable accuracy. Adoption of the proposed equations as the modified formula of stress influence coefficient in the concrete carbonation depth model for practical applications is recommended.